ارتكاز المشيمة المعيب - الدالي عصام; ناصر فيصل; عليا أمل (Latakia University Journal -Medical Sciences Series, 2019)
أجريت هذه الدراسة في مشفى الأسد الجامعي باللاذقية في قسم التوليد وأمراض النساء من 1/1/2002 ولغاية 1/9/2003 لتحديد نسبة ارتكاز المشيمة المعيب. بلغ عدد الولادات خلال هذه الفترة 3952 ولادة وعدد حالات ارتكاز المشيمة المعيب 52 حالة. بلغت نسبة ارتكاز المشيمة المعيب 1.31% من بين الولادات. العوامل التالية اعتبرت عوامل مؤهبة لارتكاز المشيمة المعيب: عمر الأم أكثر من 35 سنةـ الحمل المتعدد، سوابق القيصرية، سوابق تجريف، الولودات. نسبة إجراء القيصرية في ارتكاز المشيمة المعيب 92.31% والولادة المهبلية 7.69%. حالات ارتكاز المشيمة المعيب شخصت بواسطة التصوير بالأمواج فوق الصوتية بالمجس البطني وبلغت درجة حساسيته 95.8%. This study was conducted at AL-Assad University Hospital in Lattakia in Obstetrics and Gynecology Department between 1/1/2002-/1/9/2003 to determine the rate of placenta previa. There were 3952 deliveries, and 52 placenta previa cases. The rate of placenta previa was 1.3% from deliveries. The following are the factors contributing to placenta previa: when maternal age is higher than 35 years, multifetal pregnancy, previous cesarean section, previous curettage, multiple labor. The incidence of cesarean section for placenta previa was 92.3% and the vaginal delivery was 7.69%. The cases of placenta previa were diagnosed by abdominal ultrasound and its sensitivity was 95.8%.